PANDANGAN PASUTRI TENTANG PERKAWINAN CAMPUR BEDA AGAMA DAN PROGRAM PASTORALNYA DI PAROKI ST. CORNELIUS MADIUN - Tao, Elisabeth Yulnes; Wilhelmus, Ola Rongan (CREDENDUM: Jurnal Pendidikan Agama, 2020)
Pastoral for the Interfaith Marriage is a form of family pastoral practices conducted by Catholic Church for Catholics faithful who conducted a mixed marriage. In the Catholic Church, a mixed marriage has so far been viewed as a difficult problem due to a difference of faith between the coupels (husband and wife).Therefore, the cuples who coducted a mixed marriage basically need very much a pastoral assitance throughouttheir life. This pastoral assitance is actually given in order to enable the couplesto keeptheir promises as to be a faithful in Jesus Christ, and to do everything as far as they can to baptize and to educate their children in a Catholic manner. This scientific research conducted by applying a qualitative research method. This study aimedto analyze the understanding about the interfaith marriage of the couples in the parish of St. Cornelius Madiun who underwent an interfaith marriage; to analyze how far the Church has been carried out any pastoral assitance for those who underwent such interfaith marriage. The results of the study indicated that there were 3 (60%) respondents revealed that the Catholic Church was open to mixed marriage. They understood that mixed marriage wasa marriage conducted between a Catholic faithful and a non-Catholic faithful for various reasons such as accidentally geting a soul mate belong to different religion, married by accident, and due to a parental encouragement. As many as 5 (100%) respondents stated that they did not so far get any pastoral assistance from the Church. They arguedthat they got only a single pastoral assitance when they involved in marriage preparation course.They said that there was no ongoing pastoral assistance given to them. As many as 3 (60%) respondents expressed that their families were so happy since they were able to carry out a Catholic marriage. By carrying out the Catholic marriage their families were more eager to attend the Eucharist together, and tried their best to baptize and to educate their children in a Catholic manner.